Food Hygiene and Sanitation at the Jakarta Pondok Gede Hajj Embarkation Dormitory: Food Safety Efforts for the Hajj Pilgrims - Hayati, Fauziah; Asyary, Al; Wispriyono, Bambang; Rashid, Harunor; Memish, Z (UI Scholars Hub, 2024)
Several health risks are associated with performing Hajj pilgrimage. Food poisoning is a major cause of diarrhea and vomiting during Hajj. Food hygiene is an effort to control aspects of food, people, places, and equipment that could cause disease or health problems. This study aimed to describe food hygiene and sanitation efforts implemented in 2023 at the Jakarta Pondok Gede Hajj Embarkation Dormitory in Jakarta, implemented in 2023 to safeguard foods for the Hajj pilgrims. Using a descriptive qualitative design with a document analysis approach, this study examined activities during the pre-embarkation and embarkation periods. Pre-embarkation efforts included inspecting the kitchen environment and coaching the catering team, while during the embarkation period, activities involved checking the hygiene of catering services, inspecting foods brought by pilgrims, and assessing the quality of food and drink. This study found that the dormitory kitchen did not meet the necessary facilities and infrastructure requirements, affecting food safety. Additionally, food handlers did not fully comply with hygiene and sanitation standards. This study emphasized the necessity of meeting hygiene requirements in the kitchen, food handling, equipment, and ingredients since the pre-embarkation period.